Analisis Pengaruh Digital Customer Exprience dan Digital Service Quality Terhadap Loyalitas Nsabah Melalui Perceived Value Pada Aplikasi Digital BNI WONDR - Salni; Muhammad Nasir Hamzah; Maryam Nurdin (Sekolah Tinggi Ilmu Ekonomi (STIE) Tri Dharma Nusantara Makassar, 2026)
This study aims to analyze the influence of Digital Customer Experience and Digital Service Quality on Customer Loyalty through Perceived Value in the BNI Wondr digital application. The research employs a quantitative approach using a survey method by distributing questionnaires to customers who use the BNI Wondr application. The collected data were analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method with the assistance of SmartPLS software to examine the relationships among variables and the mediating role of Perceived Value in the research model. The results indicate that Digital Customer Experience and Digital Service Quality have a positive and significant effect on both Perceived Value and Customer Loyalty. Furthermore, Perceived Value is proven to have a positive and significant effect on Customer Loyalty and serves as a mediating variable in the relationship between Digital Customer Experience and Digital Service Quality and Customer Loyalty. These findings emphasize that well-designed digital experiences and high-quality digital services enhance customers’ perceived value, which ultimately strengthens their loyalty to the BNI Wondr digital service.